How Credit Constrained are Family-Owned SMEs in Arab Countries? - Grakolet Gourène; Zuzana Brixiova Schwidrowski; Jiří Balcar; Lenka Johnson Filipova (Global Labor Organization (GLO), 2025)
Family-owned firms account for majority of small and medium-sized enterprises (SMEs) in Arab countries, but evidence on the impact of this ownership type on access to credit in the region is scarce. Yet the issue is key for understanding barriers to the emergence of dynamic private sector and growth acceleration. Utilizing the World Bank Enterprise Surveys, this paper contributes to closing this knowledge gap by examining the links between family ownership and credit constraints of SMEs in Egypt, Jordan, Morocco, and Tunisia. We found that while family-owned firms have a higher need for credit than nonfamily-owned firms, they are more likely to be discouraged from applying for it. Due to this self-selection out of credit markets, they end up more credit constrained even though their credit application rejection rates are below those of nonfamily firms. Stronger firm governance, formal business strategies and good managerial practices can ease access to credit for family-owned SMEs.
Keywords: D22; G21; G32; 330; Family-owned SMEs; access to credit; firm governance; Arab countries